After the Hurricanes Have Gone: Stress and Decision Making When Living Alone - Carolyn S. Wilken (EDIS)
This fact sheet offers suggestions on how to control stress by offering a plan to reduce worrying. We can't do anything about the weather, but we can do something to control our worrying. This fact sheet includes some simple strategies to reduce stress and anxiety. Of course these strategies won't make all the fear go away, but by following these suggestions you can regain control over your life—no matter what your age. This document is FCS9233, one of a series of the Family Youth and Community Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date September 20, 2005.